Parental Supervisory Behavior for Unintentional Injuries among under 9 Age Group Children: A Cross-sectional Study - Pradeep Tarikere Satyanarayana; Muninarayana C.; V. Bhoomika (Current Practice in Medical Science Vol. 7, 2022)
Background: According to the World Health Organization (WHO), unintentional injuries were responsible for over majority of deaths and millions of disability-adjusted life-years with over Lower middle income countries being the major contributor. Unintentional injuries are can be easily prevented in terms of both morbidity and mortality by simple prevention measures. Unintentional injuries can happen both in outdoor and indoor settings putting the child at risk equally in both circumstances. Fatal injuries are those which require medical attention and forms only the tip of the iceberg. For every child who dies of Unintentional injury, there are many more who suffer non-fatal injuries with varying degree of disability which goes either unnoticed or underreported. Materials and Methods: This was a community-based cross-sectional study carried out for a period of 3 years from May 2019 to April 2022. Three Primary health centers of Kolar, Karnataka were randomly selected which were Aavani, Sugutur and Vemgal. 10 villages from each PHC area were selected and probability proportionate to size sampling was applied. Parental supervisory behaviour was assessed using the parent supervision attributes profile questionnaire prepared by Morrongiello BA and Corbett M was used. Results: Study showed that falls were very common followed by bruises and cuts among children aged under 9 years. Mothers who had attended Primary schooling had higher scores in the fate domain, Mothers who work for wages and their children with history of burns and animal bites had higher scores in the Protectiveness domain. Mother with her child having history of fall had higher scores in Risk Tolerance domain and Mothers with their children having history of Cuts and Grashes and also animal bites in had higher scores in Supervision domain. Conclusion: Parents both father / mother along with guardians must be educated regarding easily preventable measures to avoid unintentional injury.